Titanium dioxide nanotubes in chloride based electrolyte: an alternative to fluoride based electrolyte - S.W., Ng; F.K., Yam; K.P., Beh; Hassan, Z. (Universiti Kebangsaan Malaysia, 2014)
Often, fluoride based electrolyte was applied to synthesize highly ordered titanium dioxide nanotubes. However, in the present work, bundled titanium dioxide nanotubes were fabricated in chloride based electrolyte through electrochemical method. Structural and morphological investigations were carried out on the nanotubes synthesized under different anodization parameters. The growth mechanism of such nanotubes was elucidated and illustrated. The estimated diameter of the as-anodized nanotube was less than 150 nm while the length varied from hundreds of nanometer to microns. X-ray diffraction patterns and Raman spectra have showed anatase and rutile phases of titanium dioxide within the thermally treated samples.